2006
DOI: 10.1002/adsc.200505146
|View full text |Cite
|
Sign up to set email alerts
|

Y‐Zeolite‐Catalyzed Cyclizations of Terpenols

Abstract: Depending on the metal doped and the activation temperature, Y-zeolites can catalyze a diversity of reactions of geraniol (1), linalool (2) and nerol (3). Compound 1 can be transformed to a-and/or gcyclogeraniol (4 and 5) highly efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In addition, geranylacetone ( 2 ) is selectively transformed into α‐ambrinol ( 2c ) by a tandem sequence involving a 1,5‐diene cyclization followed by a highly diastereoselective intramolecular carbonyl‐ene reaction of γ‐cyclogeranylacetone ( 2a ). Similar cyclization results were reported almost simultaneously by a Chinese group14 using zeolites NaY and FeY.…”
Section: Resultssupporting
confidence: 87%
“…In addition, geranylacetone ( 2 ) is selectively transformed into α‐ambrinol ( 2c ) by a tandem sequence involving a 1,5‐diene cyclization followed by a highly diastereoselective intramolecular carbonyl‐ene reaction of γ‐cyclogeranylacetone ( 2a ). Similar cyclization results were reported almost simultaneously by a Chinese group14 using zeolites NaY and FeY.…”
Section: Resultssupporting
confidence: 87%
“…Geraniol or geranyl acetate (7) produced cyclogeranyl derivatives 8 as main products employing either zeolites or chlorosulfuric acid. [20][21][22] Related head-to-tail cyclizations have also been observed with sesquiterpene substrates using the conditions reported for monoterpenes 20,22 or employing superacids. 23 Strong acids seem to favor protonation of the head olen in solution.…”
Section: Introductionmentioning
confidence: 82%
“…Our belief was based on the fact that, recently, we and others had reported the efficient biomimetic cyclization of small acyclic terpenoids, such as geranyl derivatives, by adsorption within the confined environment of a zeolite. We found that zeolite NaY, a mildly acidic (containing both Lewis and Brønsted acidic sites) catalyst, promoted these cyclizations in surprisingly high yields and with good selectivities.…”
mentioning
confidence: 99%